The Fall Armyworm Spodoptera frugiperda Found on Rice Oryza sativa L. in China: Their Host Strain, Oviposition Preference and Survival Rate on Rice and Maize - Pingping Liu; Liu Zhang; Xiaoming Pu; Dayuan Sun; Huifang Shen; Qiyun Yang; Jingxin Zhang (Agronomy)
The fall armyworm (FAW), Spodoptera frugiperda, is a serious pest that threatens a range of important crops worldwide. It originated in America and rapidly dispersed throughout Africa and Asia in 2018. There are two subtypes, corn-strain (C-strain) and rice-strain (R-strain), that have different host plant preferences, and the individuals damaging maize in China were identified as C-strain. In the present study, we found FAW individuals damaging rice plants in the field of Guangdong Province, China. FAW larvae and male adults were collected, and the majority of FAWs were characterized as CO I R-strain Tpi C-strain, which is similar to the FAWs damaging maize in China. The FAW adults preferred laying eggs on maize plants more than on rice plants. Compared to those that were fed maize leaves, the FAW larvae were unable to survive when fed 4-week-old rice plants, whereas they could complete their life cycle on 2-week-old rice plants, for which the total survival rate was 8%. The pre-adult- and pupal-stage durations were prolonged, and the fecundity of adult females decreased. Thus, the FAWs found in paddy fields showed better fitness on maize than on rice in the laboratory. Owing to their low survival rate on rice plants, they were unlikely to damage paddy fields in large areas, but populations of FAWs in paddy fields should be monitored.